PROFIL LIPID DAN RESIKO KEJADIAN PENYAKIT JANTUNG KORONER (PJK) PADA WANITA MENOPOUSE DI KOTA MALANG - AAG Anom Aswin; Diniyah Kholidah; Rinawati Basuki (Jurnal Ilmu Kesehatan Masyarakat, 2012)
Coronary heart disease is characterized by a high content in addition to blood cholesterol levels, also triggered by the composition of fat in the abdominal cavity. Waist-to-hip ratio (waist to hip ratio / WHR) is one of the anthropometric measurements were used to show a pattern of obesity (central obesity) and increased risk of cardiovascular disease in women.  Cross-sectional study involving 39 women the gym in the morning in the working area of ​​Malang Health Center Arjuno present at the time of the data and are willing to be the subject of research. Waist-to-hip ratio (RLPP) determined by national standards, where the standard ratio of ≤ 0.8 for women is a safe ratio thresholds of risk factors for coronary heart disease.  Characteristics of total cholesterol was found that there was no significant difference in mean total cholesterol, LDL cholesterol and HDL cholesterol among subjects without the risk of CHD and CHD risk in subjects with significance 5%, respectively (p = 0.083, p = 0.629, p = 0.549). The results showed no significant relationship (p> 0.05) between the frequency of consumption of staple foods and vegetable side dish with RLPP on RR 0.907 (a staple food) and RR 0.194 (vegetable side dishes) (95% CI: 0.212 to 3.875 and 0.039 - 0.974). Thus, consumption of staple foods and vegetable side dishes that fat is a protective factor against the occurrence of CHD. But there is a significant correlation (p> 0.05) between the frequency of fruit and vegetable consumption with RLPP on RR 1.17 (vegetable) and RR 01,89 (fruit) (95% confidence level: 0.49 to 2.81 and 0.82 to 4.38). Thus, consumption of vegetables and fruits is a strong protective factor against the occurrence of CHD. There is a significant correlation between the levels of total cholesterol RLPP (p = 0.006) with a value of RR = 0.84 (95% CI: 0.35 to 2.04). It could be argued that individuals with normal RLPP protected category of developing CHD compared with individuals with RLPP high category. The bigger RLPP higher risk of CHD.